Peran Gender dalam Ritus Kusu Bue - Dewi, Ida Ayu Putu Kartika; Wiasti, Ni Made; ., Aliffiati (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p10, 2020)
Kusu bue rite’s a rite performed by women who have experience menstruation. Women will stay in a small house, called sao are. They cooperate with each other in every process of activity. The role of gender in the kusu bue rite also has implications for the Dona community. The formulation of the problem in this study are (1) how’s the role of gender in the implementation of the kusu bue ? (2) What are the implications of gender roles in the implementation of the kusu bue of the kusu bue rite to the Dona community? This study uses theories from Marwell and theories about the transitional rites and the inauguration ceremony of Van Gennep. Ethnographic research models,including data collection techniques through observation, interviews, literature, studies, and data analysis field. The results explained that the kusu bue ritual process lasted for eight days and seven nights. The procession begins with preparation, hen enters theses’e ritual leadig to Soromazi, to Lole Sao Are. On the second day the community performed the Waju Pare Kobho. On the third and sixth day, why would they goon a journey to find the needs of the girls. Then on the seventh day the community carried out the Bora Raa Weti and Woke Tewu rituals. On the last day the kusu bue girls will have a graduation party or wela ripe. The result of this rite to the Dona community.These implications are the implication in the social, education, deliberation,and consensusand religious fields.